The Role of E-Supply Chain Activities in Promoting Appropriate Competitive Precedents: An Exploratory Study of the Views of Managers at Carrefour Company / Erbil Governorate / Kurdistan Region / Iraq - Salih, Majid Mohammad; alrafek Alyakobi, Mohamed Sodad Awn (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to identify the electronic supply chain activities and if they can be found in Carrefour Company in Erbil / Kurdistan Region/Iraq and the rate in which theses collective activities participate in promoting the competitive priorities that are appropriate to the company's capabilities and capacity. The study also sought to answer its set questions and addressing its stated problem. A questionnaire was used as a main source for obtaining the necessary data and information and it was distributed among (60) respondents representing the directors of the divisions and departments and their assistants. The study adopted the descriptive and analytical approach to both its theoretical and practical parts to achieve its objectives and to reach answers to its questions .The relationships and impact between electronic supply chain activities and the appropriate competitive priorities were tested using the (SPSS.v.19) package. In the light of the results, the study reached a number of conclusions which indicate an effective role of the electronic supply chain activities (ERP, E-Procurement, Material Requirements Planning System, E-marketing, Customer Relations Management) in promoting the appropriate competitive priorities (Cost, Quality, Flexibility, Delivery, Innovation, and Environment) in the investigated company. On the basis of the conclusions, a number of recommendations were presented, most notably the need to give greater attention to the aforementioned activities to promote the appropriate priorities in order to enhance the competitive position of the investigated company.